Engineering of hole-selective contact for low temperature-processed carbon counter electrode-based perovskite solar cells. Issue 48 (19th November 2015) - Zhang, Fuguo; Yang, Xichuan; Cheng, Ming; Li, Jiajia; Wang, Weihan; Wang, Haoxin; Sun, Licheng
Abstract : Improved performance and stability of low temperature printable carbon counter electrode based perovskite solar cells by interfacial engineering of the hole selective contact with TPDI. Abstract : A cost-effective and solution processable hole transport material (HTM), TPDI (5, 10, 15-triphenyl-5 H -diindolo[3, 2- a :3′, 2′- c ]carbazole), was synthesized and explored as a hole selective contact material in low temperature (100 °C) and printable processed carbon counter electrode based perovskite solar cells (PSCs) for the first time. This material demonstrated excellent thermal stability, high hole mobility and appropriate energy level alignment with CH3 NH3 PbI3 and carbon, which make it a potentially excellent alternative interfacial material for PSCs. By interfacial engineering with doped TPDI, the energy barrier at the CH3 NH3 PbI3 /carbon interface was efficiently eliminated. Dramatically enhanced power conversion efficiency (PCE) of 15.5% was afforded, which is comparable to or even better than that of the reference device with 2, 2′, 7, 7′-tetrakis( N, N ′-di- p -methoxyphenylamine)-9, 9′-spirobifluorene (spiro-OMeTAD) as HTM under equivalent conditions. Besides, TPDI can also function well in its pristine form although the efficiency (13.6%) obtained is slightly lower than that with the device containing doped TPDI as the HTM. Moreover, these newly integrated noble metal-free, vacuum-free and cost effective PSCs exhibited excellent durability during the long term stability measurements for 30 days. The remarkable performance as well as dramatically reduced fabrication cost demonstrated by integrating TPDI as the HTM and cost effective commercial carbon as the cathode revealed their great potential in the scalable and practical application of PSCs.